2008
DOI: 10.1007/s00423-008-0378-3
|View full text |Cite
|
Sign up to set email alerts
|

Late outcome after surgical management of carotid body tumors from a 20-year single-center experience

Abstract: The surgical therapy of carotid body tumors shows low long-term morbidity, mortality, and recurrence rates. Cranial nerve injury is mostly temporary but a relevant procedure-related complication. Surgical resection is indicated also for small, asympomatic tumors, because of the uncomplicated resectability of these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 29 publications
1
24
0
4
Order By: Relevance
“…Locally invasive growth of these tumors subsequently leads to cranial nerve deficits along with compression symptoms like Horner's syndrome, syncope, hoarseness and dysphagia. Cranial nerve deficits particularly in 7, 9, 10, 11 or 12, can be seen in tumors that reach 5 cm in size [10][11][12]. Our patient had similar growth rate but the diameter of the lesion was only 4 cm and there was no neurological damage to above mentioned nerves.…”
Section: Discussionsupporting
confidence: 56%
“…Locally invasive growth of these tumors subsequently leads to cranial nerve deficits along with compression symptoms like Horner's syndrome, syncope, hoarseness and dysphagia. Cranial nerve deficits particularly in 7, 9, 10, 11 or 12, can be seen in tumors that reach 5 cm in size [10][11][12]. Our patient had similar growth rate but the diameter of the lesion was only 4 cm and there was no neurological damage to above mentioned nerves.…”
Section: Discussionsupporting
confidence: 56%
“…14) Octreotide scanning, a nuclear medicine imaging procedure, could also be useful for detecting the presence of multicentric or metastatic paragangliomas, and for distinguishing scar from residual tumor after surgery. 12) Although it was described that the carotid body is located in the adventitia of the carotid bifurcation, 6,12) others, 7,17,18) including the authors believe that it lies in the peri-adventitial plane. Thus, it is possible to encountering only few cases during their career.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular resection and reconstruction was inevitable in 10 tumors (15.38%) in this study. The rate of vascular repair in the literature ranged between 20% 17) and 24% (Kotelis, et al, 2009). 18) So there is a need for the presence of vascular experience among the operating team.…”
Section: Discussionmentioning
confidence: 99%
“…Sustentacular cells (type 2) are elongated cells that closely resemble Schwann cells [1]. Kaspar et al reported 52 % of the patients to be males and the average age group to be 45 years with rare cases seen in children [25,26]. These tumors are more seen in females and histologically resemble the normal architecture of the carotid body [27].…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis confining to the neck is seen in 5 % of cases with multicentricity in 25 % of cases [26]. Albsoul et al reported 58 % of the incidences on the right side of the neck [1].…”
Section: Discussionmentioning
confidence: 99%